If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4+6p+18+3p=9(p+1)+5*
We move all terms to the left:
-4+6p+18+3p-(9(p+1)+5*)=0
We add all the numbers together, and all the variables
9p-(9(p+1)+5*)+14=0
We calculate terms in parentheses: -(9(p+1)+5*), so:We get rid of parentheses
9(p+1)+5*
We add all the numbers together, and all the variables
9(p+1)
We multiply parentheses
9p+9
Back to the equation:
-(9p+9)
9p-9p-9+14=0
We add all the numbers together, and all the variables
5!=0
There is no solution for this equation
| -4=-2(x+7)-4(x+8) | | 6x-10=123-6x | | 1/2n+3=5 | | 26=2(1-6a)-5(-4a+8) | | 2x2+5=59 | | 9x+54=10x-8x-40 | | 10^x=23 | | 3.3h=3.96 | | 3(x+1)=3x+ | | n-9.3=24 | | 42=3(7a-2)+3(a+8) | | 10.5=f-0.08 | | -74=5u | | -7x-9=6x-22 | | r-7.8=13.1 | | 3(-8a+1)-3(a+2)=-57 | | p+11.8=30 | | 9x+7363893987x=1 | | 8(p-3)-2(1-4p)=-42 | | 5x–10=7x | | 45.6=16.7+b | | -7(p+8)-5(7p-2)=38 | | 8+3x-6x=38 | | -3(x-2)=-6+3x | | 11-2x+8x+5=-18 | | -7=3x^2-7x | | 7(8a+4)=-29-a | | 12x-8x+4x+9+10-3x-7=-6x-2+8x-9x-7+11+4 | | 3p-6=8(4-2p) | | -6=5x^2+3x | | 7b+9=4(6b-2) | | -32+8v=5(2+7v)-6v |